The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1073/pnas.1412592112
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activation of myosin II paralogs to correct cell mechanics defects

Abstract: Current approaches to cancer treatment focus on targeting signal transduction pathways. Here, we develop an alternative system for targeting cell mechanics for the discovery of novel therapeutics. We designed a live-cell, high-throughput chemical screen to identify mechanical modulators. We characterized 4-hydroxyacetophenone (4-HAP), which enhances the cortical localization of the mechanoenzyme myosin II, independent of myosin heavy-chain phosphorylation, thus increasing cellular cortical tension. To shift ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 48 publications
3
68
0
Order By: Relevance
“…[1] Drugs that modify cytoskeletal or nuclear architecture are often applied in cancer treatment, [8, 36] and recently, 4-hydroxyacetophenone (4-HAP) was found to alter pancreatic cancer mechanical properties by stimulating myosin-II and enhancing its cortical localization, which reduces the invasion and migration of pancreatic cancer cells by stiffening them. [8] Micropipette aspiration was used for the study measuring the cell deformability to find the efficacy of 4-HAP; however, due to its low throughput, only tens of cells were characterized to verify the drug responses. Furthermore, it was suggested that 4-HAP can be applied to other cancers, though with a micropipette aspiration approach, it is limited to test other various cancer cell lines at different stages.…”
Section: Resultsmentioning
confidence: 99%
“…[1] Drugs that modify cytoskeletal or nuclear architecture are often applied in cancer treatment, [8, 36] and recently, 4-hydroxyacetophenone (4-HAP) was found to alter pancreatic cancer mechanical properties by stimulating myosin-II and enhancing its cortical localization, which reduces the invasion and migration of pancreatic cancer cells by stiffening them. [8] Micropipette aspiration was used for the study measuring the cell deformability to find the efficacy of 4-HAP; however, due to its low throughput, only tens of cells were characterized to verify the drug responses. Furthermore, it was suggested that 4-HAP can be applied to other cancers, though with a micropipette aspiration approach, it is limited to test other various cancer cell lines at different stages.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the mechanical response of cells to their environment may be defective in some cancer cells [66]. Restoring this response may reduce the inappropriate movement of the cancer cells [67]. Studying the molecular mechanisms of cell movement in 3D extracellular matrix, rather than on 2D tissue culture plastic, is likely to provide the most efficient way to address these and other important questions (see Outstanding Questions Box) in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to treat diseases that include an element of defective mechanotransduction, putative compounds must be tested in the appropriate 3D matrix mechanics to accurately predict responses [116], and active efforts to develop compounds that selectively target key elements of the mechanotransduction pathway will be critical [117]. New mechanistic insights into how cells sense and respond to tissue mechanics will follow from the widespread implementation of in silico modeling [118] to develop complex cell-cell and cell-matrix models [92,97,106,119], and the development of 3D models to systematically tease apart the influence of diverse matrix mechanical properties, biomolecules, and genetic alterations on cell behaviors and fate in a controlled manner [120-123].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%